Thomas Edison and the electric light - Rich, Richard; Nissen, Brian, 1939-; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Family Entertainment, 2005)
This bird's eye view of Edison's legendary career takes you behind the scenes to reveal the hard work and sheer excitement of daily discoveries with "the Wizard of Menlo Park."
"Nest Complete Learning System"--Container.
"Premium website accessible through DVD-ROM"--Container.
Includes Activity Book.
Music, Lex De Azevedo.
DVD.
In English, with English or Spanish subtitles.
Keywords: Edison, Thomas A. -- 1847-1931 -- Juvenile films; Edison, Thomas A. -- 1874-1931.; Inventors -- United States -- Biography -- Juvenile films; Inventors -- Biography; Animated films; Children's films